Probation clients' barriers to access and use of opioid use disorder medications - Jessica Reichert; Lily Gleicher (BMC, 2019)
Abstract Background There is a gap between evidence-based treatment with medications for opioid use disorders (OUDs) and current practices of probation departments who supervise individuals with OUDs. Many probationers with OUDs cannot access FDA-approved medications to treat their disorders despite the strong evidence of their effectiveness. The barriers to medications for those under probation supervision include practitioners' negative attitudes toward medications, costs, stigma, and diversion risk. Probation officers have an ethical obligation to help their clients reduce barriers to access the care they need which in turn can improve their outcomes and increase public safety. Results The current study explores how probation departments respond to probationers with OUDs, focusing on the barriers to accessing OUD medications based on a survey of probation department directors/administrators (hereafter referred to as probation department leaders) in Illinois (N = 26). A majority of probation department leaders reported perceived staff barriers to their clients accessing medications. Reasons included lack of medical personnel experience, cost, need for guidance on medications, and regulations set by their organization or jurisdiction that prohibit client use of medications. Probation department leaders reported knowing less about the use of methadone and how it is administered, compared to buprenorphine and naltrexone. In addition, probation department leaders were generally more open to referring clients for treatment that include buprenorphine or naltrexone compared to methadone. Despite slightly less training or familiarity with methadone than the other medications, the number of probation department leaders who knew where to refer someone for each of the three FDA-approved medications was similar. Conclusions The current study found probation department leaders perceive some barriers to their staff linking or referring their clients to OUD medications. Study findings indicate a need for administration- and staff-level training, interagency collaboration, and policy changes to increase access to, education on, and use of, medications for probation clients. Such efforts will ultimately help probation clients with OUDs stabilize and adhere to other probation requirements and engage in behavioral therapy, which may result in positive outcomes such as reduced recidivism, increased quality of life, and reduced mortality.